Study of ionic liquids (AIL and PIL) viscosity and its functional groups under heat treatment on cutting tool surface using fourier-transform infrared spectroscopy (FTIR) - Md Yasser, Mona Alis; Embong, Zaidi; Abd Rahim, Erween; Abdullah Sani, Amiril Sahab; Kamdani, Kamaruddin (Trans Tech Publications, 2020)
This study was conducted to investigate the efficiency of Minimum Quantity Lubrication (MQL) technique by using Modified Jatropha Oil (MJO) bio-based lubricant with the presence of 10% Ammonium Ionic Liquid (MJO+AIL10%) and 1% Phosphonium Ionic Liquid (MJO+PIL1%) additives respectively at various temperature of 200 ̊C, 300 ̊C and 400 ̊C heat treatment to determine the ability to exhibit corrosion and wear throughout the process. Fourier-Transform Infrared Spectroscopy (FTIR) analysis revealed prominent peaks of functional groups in these bio-lubricants; esters (C-O) and (C=O), alkanes (C-H), hydroxide (O-H), and nitrile groups deposited on the cutting tool surface. Initially, nitrile group is detected on cutting tool surface without lubricants at 2200 to 2300 absorption band reduced to lower intensity and most likely concealed by MJO+AIL10% compared to MJO+PIL1% where the nitrile group remains reflected in FTIR spectrum. In this work, it is proved that MJO+AIL10% has higher viscosity as compared to MJO+PIL1%. in the context of functional groups and supported the previous study on MJO+AIL10% as corrosion inhibitor.